Pengaruh Komunikasi Pemasaran dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Jasa Ekspedisi PT Anugerah Tangkas Transportindo Cargo Juanda - Floren Rossa Amelia; Menur Kusumaningtyas (Jurnal of Management and Social Sciences, 2026)
This Clear information and dependable delivery performance are essential in shaping customer responses to cargo services. This study examines the extent to which marketing communication and service quality contribute to customer satisfaction at PT Anugerah Tangkas Transportindo Cargo Juanda. A quantitative survey was conducted with 60 customers who had used the company's services. Responses were collected through an online questionnaire distributed via Google Forms and WhatsApp, then processed using instrument testing and multiple linear regression analysis. The partial test results indicate that marketing communication has a significant positive effect on customer satisfaction, with a t-value of 12.417 and p < 0.001. Service quality also has a significant positive effect, with a t-value of 6.633 and p < 0.001. The simultaneous test yields an F-value of 101.545 and p < 0.001. An adjusted R-square value of 0.773 indicates that both variables explain 77.3% of the variation in customer satisfaction. The remaining 22.7% is associated with factors not included in the model. These findings emphasize the importance of aligning the information delivered to customers with the quality of cargo services they experience